2001
DOI: 10.1002/app.1764
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hot‐melt extrusion and compression molding on polymer structure organization, investigated by differential scanning calorimetry

Abstract: A blend of a pullulan polymer and 1,2,6-hexanetriol as a plasticizer were used to study the effect of melt processing techniques on the physical properties of the resulting materials. The main advantage of pullulan is its linear polysaccharide chain model structure. Hot-melt extrusion and compression molding were performed under the same temperature and pressure conditions. The materials obtained were analysed by differential scanning calorimetry. For the first time, the comparative effect of the two processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The extruded charge (extrudate) was compression-molded in a 400 ton capacity compression press as panels with the desired thickness. The residence time in the compression mold ranged from 20 s to 120 s. A three-layer morphology, i.e., the outer skin, the inner skin, and the core layers, is common for extrusion/compression-molded composites [23]. The outer skin is polymer-rich and prone to the damage caused by extrusion and compression molding stresses, and particularly critical to the assessment of the effect of exposure, especially ultraviolet radiation, which adapts to the gradient generated by polymer flow at the surface during molding.…”
Section: Methodsmentioning
confidence: 99%
“…The extruded charge (extrudate) was compression-molded in a 400 ton capacity compression press as panels with the desired thickness. The residence time in the compression mold ranged from 20 s to 120 s. A three-layer morphology, i.e., the outer skin, the inner skin, and the core layers, is common for extrusion/compression-molded composites [23]. The outer skin is polymer-rich and prone to the damage caused by extrusion and compression molding stresses, and particularly critical to the assessment of the effect of exposure, especially ultraviolet radiation, which adapts to the gradient generated by polymer flow at the surface during molding.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of an immiscible drug and matrix polymer, if the processing temperature is above the melting temperature of the active ingredient, then solid dispersions of amorphous drug domains embedded in the polymer may be formed after extrusion. Additionally, HME is a high stress process for the carrier material and the drug; as most of the matrix materials used are polymers and lipids, degradation of the polymer/lipid during the hot-melt extrusion process may occur (14,15). Therefore, accurate assessment of the physical and chemical stability of the hot-melt extruded formulations is essential.…”
Section: Introductionmentioning
confidence: 98%
“…Shear mixing of the molten mass by HME can cause drug–polymer interactions to disperse drugs and polymers at the molecular level. [ 23 ] Because the amorphous conversion of the crystalline drugs due to HME was confirmed by powder XRD it was concluded that the highest dissolution rate and supersaturation of poorly water‐soluble drugs in the dissolution test could be attributed to drug–polymer interactions occurring during HME. Therefore, a screw rotation in the individual temperature‐controlled barrel system of the HME was used to prepare a noncrystalline complex from mixtures of various drugs and a polymeric additive for pharmaceuticals by controlling temperature and flow.…”
Section: Discussionmentioning
confidence: 99%